Politeness Strategies Used by Bagas of the Pakai Hati Web Series to The Boss and Colleagues - Fethira Josephine A Joahnnis (Institute of Research and Community Outreach - Petra Christian University, 2022)
Communication is essential, therefore, to maintain a pleasant communication, “polite language” is needed. This study aims to find out the type of Politeness Strategies applied by the main character in The Pakai Hati web series. In conducting this study, the writer used Brown and Levinson’s (1987) politeness theory in analyzing the utterances spoken by the main character when conversing with his boss and his colleagues as the object of this study. In addition, this study was done using a qualitative research method. As a result, the writer found out that from 15 utterances spoken by the main character, not all Politeness Strategies are used. The main character only uses the positive and negative Politeness Strategies. The writer found out that relative power is one of the factors that makes the main character use different Politeness Sptrategy for different interlocutors.Keywords: politeness, politeness strategy